Effects of prenatal maternal stress on birth outcomes following tropical cyclone Yasi in Queensland, Australia (2011). (June 2018) - Parayiwa, Cynthia; Behie, Alison M.
Abstract: Tropical cyclones cause widespread devastation while having a negative impact on human health and well-being. Maternal exposure to prenatal environmental stressors can lead to a shift in reproductive strategies. This study aims to statistically analyse maternal and infant health risks by studying birth outcomes following maternal prenatal exposure to tropical cyclone Yasi in Queensland, Australia. Queensland state birth records collected under the Australian National Perinatal Data Collection from January 2008 to December 2012 were analysed. A confounder controlled binary logistic regression model was used to statistically compare birth weight and gestation length in cyclone Yasi affected and unaffected Queensland local government areas (LGAs). Women in cyclone Yasi affected LGAs, had a significantly higher proportion (9.6%, p  = 0.008) and significantly higher odds (OR = 1.26, 95% CI: 1.06 – 1.47) of having a preterm birth, compared to women in unaffected LGAs (7.9%). Women in affected LGAs during the year of cyclone Yasi (2011) also had a higher proportion of low birth weight births compared to women in the same LGAs during non-cyclone Yasi years (2008, 2009, 2010, 2012). Our study supported a significant increase in the proportion of preterm births recorded for women pregnant in areas severely affected by cyclone Yasi. Our findings, and similar future research, will continue to inform the development of effective post-disaster perinatal health related policies and the continued improvement of disaster risk mitigation for vulnerable groups.